2020
DOI: 10.30782/jrvm.559809
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalance of Respiratory Viruses and Pestivirus Screening in Ruminant Species in Diyarbakır Region, Turkey

Abstract: Sığır solunum sistemi hastalıkları kompleksi (BRDC) başta sığırlar olmak üzere birçok çift tırnaklı hayvan türünü etkileyen ve ülkemiz dahil olmak üzere tüm dünyada yaygın olarak görülen bir problemdir. Bu çalışmada Diyarbakır ilini temsil edecek şekilde 8 farklı ilçeden 229 sığır, 192 koyun ve 12 keçi olmak üzere toplam 433 serum örneğinde Bovine viral diarrhoea virus (BVDV), Bovine herpesvirus-1 (BoHV-1), Bovine respiratory syncytial virus (BRSV), Bovine coronavirus (BCoV) ve Bovine parainfluenza-3 (BPIV-3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…The individual seropositivity (59.78%) obtained in this study was in accordance with previous studies that reported seropositivity of BRSV in cattle ranged between 46.06% and 73% in Turkey (Yavru et al 2005 ; Yeşilbağ and Güngör, 2008 ; Kadiroğlu et al 2020 ). The highest seropositivity (73%) was found in Marmara region of Turkey.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The individual seropositivity (59.78%) obtained in this study was in accordance with previous studies that reported seropositivity of BRSV in cattle ranged between 46.06% and 73% in Turkey (Yavru et al 2005 ; Yeşilbağ and Güngör, 2008 ; Kadiroğlu et al 2020 ). The highest seropositivity (73%) was found in Marmara region of Turkey.…”
Section: Discussionsupporting
confidence: 92%
“…There is limited knowledge available about the prevalence of BRSV infection (Yavru et al 2005 ; Yeşilbağ and Güngö, 2008 ; Kadiroğlu et al 2020 ) and genetic features of BRSV strains circulating in Turkey (Hacıoğlu et al 2019 ; Timurkan et al 2019 ; Yazici et al 2020 ). Furthermore, the possible risk factors for BRSV infection in cattle have not been studied in Turkey.…”
Section: Introductionmentioning
confidence: 99%